Kappa-casein gene study with molecular markers in female buffaloes (Bubalus bubalis) - Otaviano, Antonio Roberto [UNESP]; Tonhati, Humberto [UNESP]; Desidério Sena, Janete Aparecida [UNESP]; Cerón Muñoz, Mario Fernando (FapUNIFESP (SciELO), 2005)
Caseins comprise make up about 80% of the total protein content of milk and present polymorphism with change in the amino acid sequence. Within this abundance of proteins, kappa-casein is noteworthy, since it has been associated with differences in milk yield, composition and processing. The objective of this study was to observe the existence of polymorphism in the kappa-casein gene in female buffaloes. For this purpose, blood samples from 115 female buffaloes, collected with vacutainer by needle punctionure of the jugular vein, were used. for genomic DNA extraction was done from blood samples. The PCR-RFLP and SSCP techniques demonstrated that the studied animals were monomorphic for the kappa-casein gene. Only allele B was observed in these animals, which was present in homozygosis. Therefore, it was not possible to quantify the gene action on milk yield and its constituents. The monomorphism observed in the population studied would allow the development of a method to identify mixtures of cow and buffalo milk in mozzarella cheese production, especially because, in cattle, the kappa-casein gene is polymorphic. Copyright by the Brazilian Society of Genetics.
Keywords: Buffaloes; PCR-RFLP; Polymorphism; SSCP; genomic DNA; kappa casein; molecular marker; allele; animal experiment; animal genetics; blood sampling; buffalo; cheesemaking; controlled study; DNA extraction; female; genetic polymorphism; homozygosity; jugular vein; milk production; milk yield; nonhuman; polymerase chain reaction; restriction fragment length polymorphism; single strand conformation polymorphism; Animalia; Bos taurus; Bubalus; Bubalus bubalis